Receptors and growth-promoting effects of insulin and insulinlike growth factors on cells from bovine retinal capillaries and aorta. - King, G L (1985)
It has been suggested that elevated levels of insulin or insulin-like growth factors (IGFs) play a role in the development of diabetic vascular complications. Previously, we have shown a differential response to insulin between vascular cells from retinal capillaries and large arteries with the former being much more insulin responsive. In the present study, we have characterized the receptors and the growth-promoting effect of insulinlike growth factor I (IGF-I) and multiplication-stimulating activity (MSA, an IGF-II) on endothelial cells and pericytes from calf retinal capillaries and on endothelial and smooth muscle cells from calf aorta. We found single and separate populations of high affinity receptors for IGF-I and MSA with respective affinity constants of 1 X 10(-9) M-1 and 10(-8) M-1 in all four cell types studied. Specific binding of IGF-I was between 7.2 and 7.9% per milligram of protein in endothelial cells and 9.1 and 10.4% in the vascular supporting cells. For 125I-MSA, retinal endothelial cells bound only 1.7-2.5%, whereas the aortic endothelial cells and the vascular supporting cells bound between 5.6 and 8.5% per milligram of protein. The specificity of the receptors for IGF-I and MSA differed, as insulin and MSA was able to compete with 125I-IGF-I for binding to the IGF-I receptors with 0.01-0.1, the potency of unlabeled IGF-I, whereas even 1 X 10(-6) M, insulin did not significantly compete with 125I-MSA for binding to the receptors for MSA. For growth-promoting effects, as measured by the incorporation of [3H]thymidine into DNA, confluent retinal endothelial cells responded to IGF-I and MSA by up to threefold increase in the rate of DNA synthesis, whereas confluent aortic endothelial cells did not respond at all. A similar differential of response to insulin between micro- and macrovascular endothelial cells was reported by us previously. In the retinal endothelium, insulin was more potent than IGF-I and IGF-I was more potent that MSA. In the retinal and aortic supporting cells, no differential response to insulin or the IGFs was observed. In the retinal pericytes, IGF-I, which stimulated significant DNA synthesis beginning at 1 X 10(-9) M, and had a maximal effect at 5 X 10(-8) M, was 10-fold more potent than MSA and equally potent to insulin. In the aortic smooth muscle cells, IGF-I was 10-100 times more potent than insulin or MSA. In the retinal and aortic supporting cells, no differential response to insulin or the IGFs was observed. In the retinal pericytes, IGF-I, which stimulated significant DNA synthesis beginning at 1 X 10(-9) M, and had a maximal effect at 5 X 10(-8) M, was 10-fold more potent than MSA and equally potent to insulin. In the aortic smooth muscle cells, IGF-I was 10-100 times more potent than insulin or MSA. In addition, insulin and IGF-I at 1 X 10(-6) and 1 X 10(-8) M, respectively, stimulated these cells to grow by doubling the number of cells as well. In all responsive tissues, the combination of insulin and IGFs were added together, no further increase in effect was seen. These data showed that vascular cells have insulin and IGF receptors, but have a differential response to these hormones. These differences in biological response between cells from retinal capillaries and large arteries could provide clues to understanding the pathogenesis of diabetic micro- and macroangiopathy.